Paederia foetida twig extract: a dual-purpose antidiabetic and antioxidant agent in high-fat diet-low dose streptozotocin rats - Tan, Dai Chuan; Omar, Norsuhana; Kassim, Nur Kartinee; Irfan, Muhammad; Hamid, Muhajir; Ismail, Intan Safinar; Mohd Noh, Ain’ Sabreena; Quek, Alexandra (AMG Transcend Association, 2024)
This study was conducted to determine the antidiabetic and antioxidant effect of Paederia foetida twigs in high-fat diet-low dose streptozotocin-induced Sprague Dawley rats to provide essential information for safe use in humans. Thirty-six male Sprague Dawley rats were acclimatized for a week, 6 were assigned to normal control, and 30 were induced into obesity using a high-fat diet for 4 weeks. After the obesity induction, 24 of 30 obese rats were induced diabetes by 40mg/kg streptozotocin and further divided into diabetic control and three diabetic treated groups (50mg/kg, 100mg/kg P. foetida, and 300mg/kg metformin). In the sub-chronic study, P. foetida twigs extract and metformin were orally administered to the rats for 28 days. Repeated single oral administration of 50mg/kg P. foetida twigs extract on diabetic rats for 28 days revealed this dosage as the most effective in lowering blood glucose (27.2%), comparable to metformin (23.1%). Treatment with 50mg/kg P. foetida twigs extracts displayed significant antioxidant properties that reduce oxidative stress based on the protein carbonyl levels and exhibited clinical signs of hyperglycemia and oxidative stress marker. P. foetida supplementation and metformin both reversed the clinical manifestation of type 2 diabetes.